The trouble with happiness : and other stories - Ditlevsen, Tove, 1917-1976; Goldman, Michael (Michael Favala) (United Kingdom : Penguin Books, 2022)
"A short-story collection from the acclaimed author of the Copenhagen Trilogy, never before translated in English"--
"Originally published in Danish in 1952 and 1963 by Hasselbalch, Denmark, as "Paraplyen" and "Den onde lykke""
Keywords: Ditlevsen, Tove Irma Margit, -- 1917-1976 -- Translations into English; Short stories